All Substances (drugs) are Poisons; there is None which is not a Poison. The Right Dose Differentiates a Poison and A Remedy - Rao, Bhagya Venkanna (Journal of Pharmacy Practice and Community Medicine)
Drug-induced hepatotoxicity is a potential adverse effect, contributing to the health burden, with several mechanisms involved in causing liver injury. The liver injury caused by the drug may vary with the extent of the damage, ranging from mild fatty liver to necrosis. Though uncommon and rare, it is contributing to morbidity and mortality in the general population and remains a potential complication for most of the prescribed drugs.